FIRST-ORDER SELFADJOINT SINGULAR DIFFERENTIAL OPERATORS IN A HILBERT SPACE OF VECTOR FUNCTIONS - (:unkn) unknown (TEXAS STATE UNIV, 2017)
In this article, we give a representation of all selfadjoint extensions of the minimal operator generated by first-order linear symmetric multipoint singular differential expression, with operator coefficient in the direct sum of Hilbert spaces of vector-functions defined at the semi-infinite intervals. To this end we use the Calkin-Gorbachuk method. Finally, the geometry of spectrum set of such extensions is researched.
Keywords: Multipoint singular differential expression; deficiency indeces; symmetric and selfadjoint differential operator; spectrum